A dinâmica do crescimento das exportaç\~oes do agronegócio brasileiro - Rebecca Lima Albuquerque Maranh\~ao; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The main objective in this study is to analyze the sources of growth of Brazilian exports of soybeans, maize, sugar, wheat, orange, cotton, coffee and meat (beef, pork and poultry) during 1992 to 2013. The methodological procedures involved the application of Constant Market Share model to decompose the exports growth as the effects of global growth, exports composition, market distribution and competitiveness. In the 1990s, global growth was relatively low; however, with the trade liberalization and monetary stabilization, Brazilian exports achieved positive rates driven by the exports composition and market destination. From 2000s onwards, the growth of world trade was very significant, driven by increased demand from emerging countries, which provided the commodity boom. The favorable performance of Brazilian agricultural exports was not only related to global growth, but also to the competitive gains that are associated with technological modernization which promoted the expansion of productivity. However, when comparing the first decade with the second, there was a reduction in competitiveness, which indicates the need to encourage productive investments.
Keywords: Q13; Q17; F10; 330; foreign trade; growth; agriculture; market share